Addressing Genderqueer Identities Through Education (Prithvi Academic Journal, 2025)
This study aimed to identify the challenges faced by genderqueer individuals and members of the LGBT community, while also proposing educational strategies to address these issues. Participants were selected using a purposive sampling technique. Data collection methods included interviews, observations, and field notes, while secondary data were gathered from literature reviews, previous research studies, published materials, and online resources. Data presentation and analysis involved verbatim transcription, paraphrasing, and reflective and reflexive processes, with queer theory serving as the framework for interpreting the findings. The literature and collected data affirm that the LGBT community faces numerous challenges, particularly in educational settings. These include misconceptions related to gender stereotypes and sexuality, involvement in the sex industry, gender-based violence, identity struggles, conflicts between rights and relationships, social exclusion, consumerist pressures, barriers to school enrollment, workplace and housing discrimination, polysexuality-related stigma, sexual violence, and legal issues surrounding same-sex marriage or partnerships. To effectively address these challenges, this study calls for the development of policies and laws that are inclusive of diverse sexual orientations and gender identities; the dismantling of gender binaries, stereotypes, stigma, and superstitions; increased budget allocations for educational opportunities; the implementation of school-based sexuality education (SBSE) and comprehensive sexuality education (CSE); the creation of LGBT-friendly school environments; and the establishment of a commission dedicated to advocating for LGBT rights.